Ethiopia's commitment towards achieving sustainable development goal on reduction of maternal mortality: There is a long way to go. (December 2021) - Ayele, Asnakew Achaw; Tefera, Yonas Getaye; East, Leah
Maternal mortality reduction has been recognized as a key healthcare problem that requires prioritizing in addressing. In 2015, the United Nations has set Sustainable Development Goals to reduce global maternal mortality ratio to 70 per 100, 000 live births by 2030. Ethiopia as a member country has been working to achieve this Sustainable Development Goals target for the last decades. In this article, we discussed Ethiopia's commitment towards achieving Sustainable Development Goals in maternal mortality. Furthermore, the trends of maternal mortality rate in Ethiopia during Millennium Development Goals and Sustainable Development Goals are also highlighted. Although maternal mortality has been declining in Ethiopia from 2000 to 2016, the rate of death is still unacceptably high. This requires many efforts now and in future to achieve the Sustainable Development Goals target by 2030.